Women participation in corporate boards: quantile regression approach. (25th January 2023) - Arora, Akshita; Soni, Tarun Kumar
Our study unfolds the stylised facts on women directorship in corporate boards for Indian listed companies. We analyse women directorships across different sectors, firm age groups, different categories of board sizes and year-wise and then investigate the impact of women directors on firm performance using panel fixed effects and pooled quantile regression approach. The panel data framework has been structured for a dataset of 442 companies for the time period 2013-2019. The women engagement in boardroom has advanced from meagre 5% in 2013 to 14% in 2019 after the introduction of gender-based quota in India. The empirical results substantiate that the impact of women directors on firm performance is weak. From the policy perspective, it is evident that amendments in the regulatory framework in board composition have led to more participation of women in leadership positions. However, it is suggested that further reforms are needed for encouraging women directors to act independently and foster more diversity in Indian boardrooms.